2015
DOI: 10.4315/0362-028x.jfp-15-121
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Foodborne Pathogens in Freshwater Fish in Latvia

Abstract: The aim of this study was to detect the prevalence of Salmonella spp., Listeria monocytogenes, and Yersinia enterocolitica in freshwater fish in Latvia. In total, 235 samples, including freshly caught fish from fives lakes (n = 129) and fish from retail markets (n = 106), were collected from April 2014 to December 2014 in Latvia. Samples were tested according to International Organization for Standardization methods. No Salmonella spp. were found in fresh fish from lakes or in commercially available fish. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Serotype 4b, 1/2a, and 1/2b account for 95% of the strains isolated from human listeriosis ( Cartwright et al, 2013 ; Althaus et al, 2014 ). In this study, the majority of L. monocytogenes belonged to serogroup I.1 (serotype 1/2a, 38.89%), II.2 (serotype 1/2b, 34.72%), and III (serotype 4c, 22.22%), which is consistent with the previous results obtained in fish from several countries ( Fallah et al, 2013 ; Jamali et al, 2015 ; Terentjeva et al, 2015 ). Wang et al (2015) reported serotype 1/2b (belonged to ST87 and ST3) with a frequency of 64.3% of L. monocytogenes was predominant in human listeriosis cases in China, similar results was also reported in Zigong, Sichuan province, conducted by Wang et al (2018) , indicating potential hypervirulent isolates were present in aquatic products in China.…”
Section: Discussionsupporting
confidence: 92%
“…Serotype 4b, 1/2a, and 1/2b account for 95% of the strains isolated from human listeriosis ( Cartwright et al, 2013 ; Althaus et al, 2014 ). In this study, the majority of L. monocytogenes belonged to serogroup I.1 (serotype 1/2a, 38.89%), II.2 (serotype 1/2b, 34.72%), and III (serotype 4c, 22.22%), which is consistent with the previous results obtained in fish from several countries ( Fallah et al, 2013 ; Jamali et al, 2015 ; Terentjeva et al, 2015 ). Wang et al (2015) reported serotype 1/2b (belonged to ST87 and ST3) with a frequency of 64.3% of L. monocytogenes was predominant in human listeriosis cases in China, similar results was also reported in Zigong, Sichuan province, conducted by Wang et al (2018) , indicating potential hypervirulent isolates were present in aquatic products in China.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, a study in Iran reported that 14.16% of retail rainbow trout were positive for L. monocytogenes compared to the 4.16% positive rate of fish samples collected from ponds on fish farms (Rezai, Ahmadi, & Salimi, 2018). Listeria monocytogenes was detected in 26% of retail and 2% of wild‐caught freshwater fish in Latvia (Terentjeva et al., 2015). Fish skin is considered one primary contamination source.…”
Section: Microbiological Safety Of Fish and Fish Productsmentioning
confidence: 99%
“…The International Commission on Microbiological Specification for Foods suggests microbiological criteria for fresh fish (only aerobic plate count and E. coli ) ( 8 ), but these are not legally enforced and the lack of legislated safety criteria creates potential health risk for consumers. The necessity of monitoring contamination of food fish caused by pathogenic bacteria has been confirmed by other authors ( 13 , 23 , 30 , 31 ).…”
Section: Introductionmentioning
confidence: 67%
“…Food fish contain bacteria pathogenic to humans, like Listeria monocytogenes , Salmonella spp., Staphylococcus aureus , and Escherichia coli ( 3 , 12 , 13 , 23 , 28 , 30 , 31 ), and therefore consumption may be entailed risk for consumers. The consumption of raw or insufficiently heat-treated fish causes most outbreaks of food poisoning ( 13 ).…”
Section: Introductionmentioning
confidence: 99%